The Playing of the Child Performer with Orixás:: artistic and afro-referenced experiences - Braga, Lia; Alves, Teodora (Revista Brasileira de Estudos da Presença, 2022)
This article presents excerpts from a master’s dissertation in Performing Arts about performances of children’s playing bodies, in Early Childhood Education, based on the Orixás universe. It initially reveals the participating children (NEI/Cap/UFRN), dialoguing with author(s) such as Marina Marcondes Machado (2010a; 2010b; 2015). It develops intersections between performance and childhoods, articulating an afro-playful methodology with the children’s protagonism. The artistic, afro-referenced and performative narratives of the authors raise contemporary considerations, providing findings for this discussion.